2000
DOI: 10.4049/jimmunol.164.10.5352
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of RANTES Chemokine Gene Expression Requires Cooperativity Between NF-κB and IFN-Regulatory Factor Transcription Factors

Abstract: Virus infection of host cells activates a set of cellular genes, including cytokines, IFNs, and chemokines, involved in antiviral defense and immune activation. Previous studies demonstrated that virus-induced transcriptional activation of a member of the human CC-chemokine RANTES required activation of the latent transcription factors IFN-regulatory factor (IRF)-3 and NF-κB via posttranslational phosphorylation. In the present study, we further characterized the regulatory control of RANTES transcription duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
209
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(220 citation statements)
references
References 43 publications
(46 reference statements)
11
209
0
Order By: Relevance
“…Expression of RANTES requires cooperative effect between NF-B and IRF3/7 (40). The near complete inhibition of RANTES in TRIF-deficient macrophages and mice lung is likely due to an impaired NF-B activation because IRF activation was not observed after P. aeruginosa infection in this study.…”
Section: Figurementioning
confidence: 56%
“…Expression of RANTES requires cooperative effect between NF-B and IRF3/7 (40). The near complete inhibition of RANTES in TRIF-deficient macrophages and mice lung is likely due to an impaired NF-B activation because IRF activation was not observed after P. aeruginosa infection in this study.…”
Section: Figurementioning
confidence: 56%
“…IRF-7 and IRF-3 (not found as modified in the array; data not shown) play critical roles in the innate response to a viral infection [53] and IRF-7 also contributes to IFN-γ-mediated apoptosis [55]. Among the downstream genes regulated by IRF-7, in cooperation with NF-κB, is the CC chemokine RANTES [56]. We observed that PIC increased RANTES expression by more than 100-fold.…”
Section: Discussionmentioning
confidence: 75%
“…hTERT-HME1-derived cells, untreated or treated with TNF-␣ for 4 h, were lysed in EMSA lysis buffer, supplemented with protease inhibitors. The probe was the NF B consensus sequence (top strand, 5Ј-TTTTGGAAACTCCCCTTAGGGGA TGCCCCT-3Ј) from the RANTES promoter (Nelson et al 1993;Genin et al 2000). Labeled probe (10 4 DPM) was used in each binding reaction.…”
Section: Emsasmentioning
confidence: 99%